Contextual Brand Valuation From Fundamental Issues and Analysis of the State of the Art to a Systematic Integrated Approach to Brand and Intellectual Property (E)Valuation - Riemann, Eva (Munich Intellectual Property Law Center - MIPLC, 2012)
Intangible Assets such as brands and other intellectual property (IP) are highly contextual and unique. There exist hardly any functioning market mechanisms for IP. For these reasons, IP valuation for strategic and prognostic, i.e. future-related, purposes is highly complex. This work aims at making a contribution to facilitate better handling of this complexity. It therefore firstly illuminates basic aspects of value which apply to all IP, before specifics of trade marks and brands are dealt with. The introduction of a new approach to IP valuation as well as an overview of legal dimensions of brand value constitute further key aspects of the work.